Pushing and Establishing New Frontiers: An Examination of Publication Patterns From 2015-2023 in the Journal of Student-Run Clinics - Nguyen, Oliver T; Rumenapp, Joseph C; Lee, David; Patel, Hardik; Chen, Kevin; Major, Kendall (Journal of Student-Run Clinics, 2024)
Background: The Journal of Student-Run Clinics (JSRC) has published research from student-run clinics (SRCs) for almost ten years. However, to date, no study has aimed to summarize publishing trends observed at JSRC. Thus, we aimed to characterize these JSRC publications in order to identify patterns in published research topics, identify research gaps, and inform future research priorities. Methods: We adapted scoping review methodology and included all articles published in the JSRC from 2015 to 2023. For each article, we assessed for publication year, article type, university affiliated with the SRC, region of the United States (US) the SRC is located in, disease focus, outcomes studied, data collection methods used, sample size, interventions involved, analytic approaches used, and concept domains involved. Concept domains were determined using a taxonomy from the Agency for Healthcare Research and Quality (AHRQ) to identify patterns in topical content from published articles. Results: This review included 167 articles. Over time, we observed an increasing trend of overall publication volume (e.g., 5 in 2015 vs 23 in 2023). Studies typically occurred in the primary care context with fewer studies in other outpatient specialties (e.g., ophthalmology, physical therapy). The most common domains were workforce (21.3%), workflows (17.4%) and practice/quality improvement (17.4%). Empirical studies typically used surveys (52.1%) or chart reviews of patient records (38.5%) for data sources. Less than half of the studies aimed to assess the impact of an intervention. Conclusion: This review highlighted significant strides made on research in SRCs. Future studies reporting intervention may benefit from adhering to established reporting guidelines. Additional studies are needed across several areas, including understanding the impact of non-primary care SRCs, assessing quality of care and clinical outcomes, and employing qualitative and/or mixed methods approaches when studying interventions’ impact on patients and volunteers.